2019
DOI: 10.1016/j.jhsg.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in the Battle Against the Opioid Crisis in Hand Surgery: A Review

Abstract: The opioid epidemic is the subject of much debate and research within all medical fields. Notable work has been done in hand surgery. The purpose of this article is to review the recent literature as it pertains to opioid use in hand surgery. The scope of the current problem is identified and mitigating strategies are described. More studies are necessary to evaluate the efficacy of these strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Our findings are in keeping with the overall decline in the national opioid prescribing rate from 2012 to 2017 to the lowest rate in the past 10 years at 58.7 prescriptions per 100 persons. 24 Although our study cannot thoroughly assess the effects of specific legislation or policies, given the considerable heterogeneity in state-led interventions, previous literature has suggested that opioid-limiting regulations have been effective in changing prescribing patterns. For example, Reid et al 25 examined the impact of opioid-limiting laws on postoperative opioid prescribing and secondary outcomes after anterior cervical diskectomy and fusion by comparing a cohort of patients pre-law (December 1, 2015, to June 30, 2016) and post-law (June 1, 2017, to December 31, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings are in keeping with the overall decline in the national opioid prescribing rate from 2012 to 2017 to the lowest rate in the past 10 years at 58.7 prescriptions per 100 persons. 24 Although our study cannot thoroughly assess the effects of specific legislation or policies, given the considerable heterogeneity in state-led interventions, previous literature has suggested that opioid-limiting regulations have been effective in changing prescribing patterns. For example, Reid et al 25 examined the impact of opioid-limiting laws on postoperative opioid prescribing and secondary outcomes after anterior cervical diskectomy and fusion by comparing a cohort of patients pre-law (December 1, 2015, to June 30, 2016) and post-law (June 1, 2017, to December 31, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are in keeping with the overall decline in the national opioid prescribing rate from 2012 to 2017 to the lowest rate in the past 10 years at 58.7 prescriptions per 100 persons. 24…”
Section: Discussionmentioning
confidence: 99%